PENGARUH PENGGUNAAN MEDIA DIGITAL BOOK TERHADAP KEMAMPUAN MENULIS CERITA PENDEK SISWA KELAS V SD NEGERI 123 BANTI KABUPATEN ENREKANG - Siska; Munirah; Haslinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using digital book learning media on the short story writing ability of fifth grade elementary school students. This study used a pre-experimental method with a one group pretest-posttest design. The study was conducted at SD Negeri 123 Banti, Enrekang Regency with 13 fifth grade students as research subjects. Data collection was carried out through short story writing ability tests, student activity observation sheets, and student response questionnaires on the use of digital book media. Data analysis techniques used included descriptive analysis and inferential analysis, namely normality tests and hypothesis tests. The results of the study showed that the use of digital book learning media had a significant effect on students’ short story writing ability. This was evidenced by an increase in students’ average score from 54.62 in the pretest to 86.38 in the posttest. The results of the hypothesis test showed that the t-count value was greater than the t-table, namely 15.372 > 1.782, and the significance value (2-tailed) <0.001 which was smaller than 0.05. Thus, it can be concluded that H0 is rejected and H1 is accepted, indicating that digital book learning media has an effect on the short story writing skills of fifth-grade students at SD Negeri 123 Banti, Enrekang Regency